Distribution of spiders in Malaysia with special emphasis of the systematics and ecology of the orb-web spider (Araneae: Tetragnathidae) / Muhammad Dzulhelmi Muhammad Nasir - Muhammad Dzulhelmi , Muhammad Nasir (2016)
This study aimed to determine the diversity and distribution of spider species that can be found in selected locations on the west coast of Peninsular Malaysia. This study also aimed to determine the systematics and ecology of tetragnathid species in Malaysia. To document the spider diversity, specimens were collected from 11 selected locations from Peninsular Malaysia. Then, samplings of tetragnathid species that build orb-web were conducted in ten selected localities that represented ten habitat types in Malaysia. These samplings were conducted between January 2012 and December 2013. From the total number of spider species recorded in Peninsular Malaysia, additional 219 species including 70 newly recorded species were managed to be compiled. This documentation added up to a total of 644 spider species currently recorded in Peninsular Malaysia. From the specimens’ collection, only 44.12% of tetragnathid species were collected out of total number of tetragnathid species recorded in Malaysia. This included 15 recognized species and three newly described species (i.e. Leucauge sabahan, Opadometa kuchingensis and O. sarawakensis). From the morphological diagnoses, this study identified that Leucauge and Opadometa species share many similar features, as well as in Mesida and Tylorida, although the members from the genus Tetragnatha is considered very distinct morphologically. The 14 morphological characters selected were useful for constructing the data matrix, dichotomous keys and diagnoses of tetragnathid species found in this country. The phylogenetic trees reconstructed using mitochondria-encoded cytochrome oxidase I (COI) and nuclear-encoded 18S rRNA (18S) genes of Malaysian tetragnathid species produced almost identical tree topologies with minor differences. The tree topologies corroborate with the internal relationship hypothesis of the family Tetragnathidae. They form two distinct lineages that are relative to subfamily Leucauginae and Tetragnathinae which is coherent with morphological characteristics. Both genes were useful in resolving the monophyletic relationships of tetragnathid species. However, the COI gene was more informative than 18S gene in resolving intra- and inter-specific relationships of tetragnathid species found in Malaysia. Meanwhile, web characteristics of twelve species from four genera (Leucauge, Mesida, Tetragnatha and Tylorida) occurring in Malaysia were investigated. Principal component analysis revealed that some tetragnathid species that coexist within the same habitat formed two close clustering in the PCA plots. Other tetragnathid species formed two separate clusters in the PCA plots due to wide variations in their web characteristics. Web-sizes and web-sites in relation to the heights from ground were the most important variables in the web characteristics. This finding suggests that tetragnathid spiders exhibit niche partitioning and their web characteristics determine the web placement in a particular habitat type. Orb-web spiders select and build their first orb-webs as early as during the juvenile stage. The relationships between the morphology and web characteristics of four tetragnathid species (Leucauge argentina, L. celebesiana, Mesida gemmea and Tylorida ventralis) was conducted. The morphological characters showed strong correlation with web sizes. However, no correlation was found between morphological characteristics and the number of spirals, number of radii, web angles and web-sites of the four tetragnathid species. Factors that reflect web characteristics of different body sizes are likely to be influenced by environmental factors. Changes of other web characteristics could be a response to the requirements of a particular situation within the habitat types. The information obtained from this present study will give an insight for other spider studies worldwide and particularly in Malaysia.